Managing renal complications in multiple myeloma - Fotiou, D.; Dimopoulos, M.A.; Kastritis, E. (Expert Review of Hematology, 2016)
Introduction: About 20–40% of patients with multiple myeloma (MM) will present with some degree of renal impairment (RI) and about 25% of patients will experience RI at later disease stages. Patients with MM and RI have poorer overall survival and are at higher risk of early death. Areas covered: The mechanisms of acute renal damage in MM are covered and the issues around diagnosis and renal evaluation response are discussed. The importance of optimal supportive care is stressed and the role and effectiveness of different anti-myeloma agents covered including the role of high cut-off hemodialysis, autologous stem cell transplantation and kidney transplant. Expert commentary: Outcomes of patients with RI and rates of renal recovery have improved with the use of novel anti-myeloma agents. Bortezomib-dexamethasone backbone regimes (±third agent) are the current first choice in newly diagnosed patients. In relapsed/refractory disease additional treatment options include newer novel agents. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: bortezomib; Carfilzomib; high-cut off hemodialysis; IMiDs; multiple myeloma; myeloma cast nephropathy; renal impairment